Synthesis of TiO2 nanosized powder photocatalyst via soft-gel method for bacteria inactivation application - Mohd Daud, Farah Diana; Sopyan, Lis; Mel, Maizirwan (2010)
Titanium dioxide (TiO2) is the most widely used photocatalyst and has been applied for water and air purification and disinfection of microorganism. Anatase structured TiO2 is a wide bandgap (3.2 eV) semiconductor which, under UV light, is able to degrade chemicals and cell components of microorganisms. In this study, TiO2 nanopowder photocatalyst was synthesized by sol-gel process using a titanium chelate compound, titanium (di-isopropoxide) bis(acetylacetonate) (PTP) as the precursor. The precursor was hydrolyzed under an acidic catalyst condition, followed by reflux for 15 minutes and 1 hour. The precipitate powder obtained after filtration was calcined at 400°C. XRD analysis confirmed that the TiO2 powders A (15 minutes reflux) and B (1 hour reflux) have strongest peak at 25° which indicates anatase crystal structure. The particle size of powder A was smaller than the Powder B as proved by calculation using Scherrer’s equation. The crystallization temperature of TiO2 powder A was higher due to its smaller particles that needed more heat to crystallize than powder B as confirmed by TG/DTA. FESEM analysis showed powder A have homogenous spherical shape, contrast to powder B showing inhomogenous spherical shape and connected particle. The TiO2 photocatalyst activity in killing bacteria was investigated for 5 hours by varying the concentration of TiO2 and UV light intensity.